2022
DOI: 10.1002/adsc.202200835
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress of Electron‐Withdrawing‐Group‐Tethered Arenes Involved Asymmetric Nucleophilic Aromatic Functionalizations

Abstract: Electron-withdrawing groups (EWG) have emerged as a powerful tool for the activation of various arenes to promote nucleophilic dearomative additions for the construction of complicated chiral cyclic structures under asymmetric catalytic systems. Nitro-indoles, nitro-benzofurans/benzothiophenes, and related nitro-heteroarenes are widely applied in the reaction with various nucleophiles to construct various enantioenriched polycyclic skeletons via the asymmetric dearomatization process. Meanwhile, the electron-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 116 publications
0
5
0
Order By: Relevance
“…In recent years, extensive research on the dearomative cyclization reaction of 2-nitrobenzofuran has revealed the significant potential of this strategy in the construction of polycyclic compounds containing a 2,3-dihydrobenzofuran core ( Scheme 1 , top) [ 26 , 27 , 28 ]. Among the numerous transformations with respect to the dearomative cyclization reaction of 2-nitrobenzofurans, the carbon nucleophile-triggered dearomative (3 + 2), (4 + 2), and (5 + 2) cyclization reactions have been extensively studied [ 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, extensive research on the dearomative cyclization reaction of 2-nitrobenzofuran has revealed the significant potential of this strategy in the construction of polycyclic compounds containing a 2,3-dihydrobenzofuran core ( Scheme 1 , top) [ 26 , 27 , 28 ]. Among the numerous transformations with respect to the dearomative cyclization reaction of 2-nitrobenzofurans, the carbon nucleophile-triggered dearomative (3 + 2), (4 + 2), and (5 + 2) cyclization reactions have been extensively studied [ 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…In sharp contrast, the research with respect to electron-deficient heteroaromatic compounds remains relatively underdeveloped. Because the first palladium-catalyzed asymmetric dearomative [3+2] cycloaddition reaction of simple nitroarenes and trimethylenemethane was reported in 2014 by Trost and coworkers [ 21 ], the research on the catalytic asymmetric dearomatization reaction of electron-deficient nitroheteroarenes, including nitroindoles, nitrobenzofurans, and nitrobenzothiophenes, had attracted great interest from the synthetic organic chemistry community [ 22 , 23 , 24 , 25 , 26 ]. In this research area, the use of electron-deficient nitroheteroarenes as dipolarophiles for the asymmetric dearomative [3+2] cycloaddition reaction with various azomethine ylides has been sporadically reported.…”
Section: Introductionmentioning
confidence: 99%
“…Herein, we wish to reported the initial finds toward this protection group migration/aza-1,6-Michael addition sequences. In recent years, there have an increasing number of reports on 3-nitroindoles as electrophiles in the reaction with various nucleophiles for the construction of diverse indolines via dearomative process [29][30][31][32][33]. Among these reactions, 3-nitroindoles are characterized by their readiness to be attacked by nucleophiles at the C2-position and sequentially trapped by electrophiles with the C3-position for the synthesis of indoline-containing polycyclic compounds (Scheme 2a).…”
Section: Introductionmentioning
confidence: 99%